Evaluation of heavy metal status of water and soil at Ikogosi warm spring, Ondo State Nigeria (2009)
The concentration levels of selected heavy metals, (Cu, Cd, Zn, As and Cr) were determined in the soil (ug/g) and water (ppm) samples collected at Ikogosi Warm Spring, Ekiti State, Nigeria. After digestion, Atomic Absorption Spectrophotometer (AAS) was employed for the determination. The study area was at Latitude of 7° 35' 38.9'' Longitude of 4° 58' 52.6'' and at average elevation of 479m above mean sea level (msl). The average concentrations (ug/g) of the heavy metals in the soil are Cu (5.29), Cd (1.50), Zn (46.72), As (10.50) and Cr (339.78). The average concentrations (ppm) of the heavy metals in the water are Cu (4.8), Cd (0.15), Zn (4.17), Ar (0.57) and Cr (1.46). The mercury was below detection limit for both soil and water samples. In the overall, the average concentration of chromium is the highest in the soil with concentration of 339.78 ug/g (an average of 84.27%) and cadmium having the lowest with value of 1.50 ug/g (an average of 0.37%). When average concentration of heavy metal in the water was considered, copper had the highest level with concentration of 4.80ppm (an average of 43.01%) and cadmium had the lowest concentration with value of 0.15ppm (an average of 1.43%). Comparison of these results showed that, their mean levels are within the standard values obtained in Nigeria and some developed countries.